Efficiency of DNA repair systems in the optimization of the seed priming process in sugar and red beet - Boubriak, I. I.; Dmitriev, O. P.; Boubriak, O. A.; Grodzinsky, D. M.; Akimkina, T. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Osmopriming is widely used in the world to improve the seed material quality of agricultural and horticultural species. This process can be further tuned, if we can identify risks from overpriming and find reliable molecular markers for the priming optimization. We analyzed an integrity of DNA after different regimes of priming for sugar and red beet. It turned out that all treatments lead to an increased level of high molecular weight DNA in cells because of the DNA repair function. However, during the drying of primed seed, we also see the accumulation of degraded (low molecular weight) DNA, whose concentration is proportional to the priming intensity. Using the ratio content values of high to low molecular weight DNA in the embryos of treated seeds, it is possible to estimate the priming quality and predict (to a certain extent) the risk of overpriming. It is also shown that the reparative DNA synthesis in the first hours of germination reflects the DNA repair intensity for the damage accumulated during priming. Efficiency of repair in primed beet seed can be tested by the introduction of an additional DNA damage into embryo cells via gamma-irradiation. Potential capability of repair systems to recover from such additional DNA damage together with measurements of DNA-ligase I induction can be used as a reliable molecular marker for the priming optimization of sugar and red beet.